Lower limb alignment and laxity measures before, during and after total knee arthroplasty: A prospective cohort study. (August 2017) - Clarke, Jon V.; Deakin, Angela H.; Picard, Frederic; Riches, Philip E.
Abstract: Background: This study compared knee alignment and laxity in patients before, during and after total knee arthroplasty, using methodologically similar procedures, with an aim to help inform pre-operative planning. Methods: Eighteen male and 13 female patients were recruited, mean age 66 years (51–82) and mean body mass index of 33 (23–43). All were assessed pre- and postoperatively using a non-invasive infrared position capture system and all underwent total knee arthroplasty using a navigation system. Knee kinematic data were collected and comparisons made between preoperative clinical and intraoperative measurements for osteoarthritic knees, and between postoperative clinical and intraoperative measurements for prosthetic knees. Findings: There was no difference in unstressed coronal mechanical femoral-tibial angles for either osteoarthritic or prosthetic knees. However, for sagittal alignment the knees were in greater extension intraoperatively (osteoarthritic 5.2° p < 0.001, prosthetic 7.2° p < 0.001). For osteoarthritic knees, both varus and valgus stress manoeuvres had greater angular displacements intraoperatively by a mean value of 1.5° for varus (p = 0.002) and 1.6° for valgus (p < 0.001). For prosthetic knees, only valgus angular displacement was greater intraoperatively (0.9°, p = 0.002). Interpretation: Surgeons performing total knee arthroplasties should be aware of potential differences in alignment and laxity measured under different conditions to facilitate more accurate operative planning and follow-up. Highlights: Knee alignment and laxity before, during and after knee arthroplasty were determined. No difference in coronal alignment was evident. Greater knee extension occurred intra-operatively than in the clinic.